Potential impact of the Affordable Care Act's preventive services provision on breast cancer stage: A preliminary assessment. (August 2017) - Silva, Abigail; Molina, Yamile; Hunt, Bijou; Markossian, Talar; Saiyed, Nazia
Highlights: As of January 1, 2011, the Affordable Care Act (ACA) eliminated copayments for mammography and other recommended preventive services. A national cancer registry was used to examine the impact of the ACA's preventative services provision on breast cancer stage and racial/ethnic disparities in stage. All three racial/ethnic groups experienced a shift toward stage I breast cancer and a small reduction in stage disparities was observed. Preliminary data suggest that the ACA's elimination of copayments for preventive services such as cancer screening may have a meaningful impact on cancer outcomes and disparities. Abstract: Introduction: The Affordable Care Act's (ACA) preventive services provision (PSP) removes copayments for preventive services such as cancer screening. We examined: 1) whether a shift in breast cancer stage occurred, and 2) the impact of the provision on racial/ethnic disparities in stage. Materials and methods: Data from the National Cancer Database were used. The pre- and post-PSP periods were identified as 2007–2009 and 2011–2013, respectively. Proportion differences (PDs) and 95% confidence Intervals (CIs) were calculated. Results: All three racial/ethnic groups experienced a statistically significant shift toward Stage I breast cancer. Pre-PSP, the black:white disparity in Stage I cancer was −9.5 (95% CI: −8.9, −10.4) and the Latina:white disparity was −5.2 (95% CI: −4.0, −6.1). Post-PSP, the disparities improved slightly. Discussion: Preliminary data suggest that the ACA's PSP may have a meaningful impact on cancer stage overall and by race/ethnicity. However, more time may be needed to see reductions in disparities.